Correlates of readmission risk and readmission days in a large psychiatric hospital in Guangzhou, China. (20th August 2013) - Zhou, Yanling; Ning, Yuping; Fan, Ni; Mohamed, Somaia; Rosenheck, Robert A.; He, Hongbo
Abstract Introduction For many patients with psychiatric disorders, the course of illness is characterized by frequent relapses, resulting to re‐hospitalization and high costs. While the correlates of readmission have been extensively studied in developed countries, few studies have examined readmission in low‐ and middle‐income countries where bed supply is limited. Methods Using administrative data from the Guangzhou Psychiatric Hospital (GPH), we used Cox regression models to evaluate the relationship among age, gender, index length of stay (LOS), and the number of previous admissions to post‐discharge readmission risk. Linear regression is used to evaluate predictors of total hospital days during the year after the index discharge. Results Between April 1, 2010 and March 31, 2011, 2, 525 patients were discharged with International Classification of Diseases, 10th Revision psychiatric diagnoses from GPH, with an average LOS of 64.2 (SD = 69.0), and 317 (12.4%) were readmitted in the following year. Survival analysis showed older age (P < 0.05), and the number of previous hospitalizations (P < 0.01) were significant predictors of the risk of readmission but not diagnosis or LOS. The number of previous admissions was the only predictor of total bed days of psychiatric care at GPH in the year following the initial discharge. Discussion Shortened LOS was not associated with increased readmission risk or post‐discharge hospital days. Rather, the number of past hospitalizations was the major predictor of both readmission risk and post‐discharge hospital days of psychiatric care, and such patients deserve special attention. Lowering LOS may be justified, allowing funds to be redeployed to outpatient or community‐based care.